Flecainide toxicity in a preterm neonate with permanent junctional reciprocating tachycardia - Karmegaraj, Balaganesh (Ann Pediatr Cardiol, 2017)
We report a case of flecainide toxicity in a premature neonate with permanent junctional reciprocating tachycardia which was managed successfully by reversal of the sodium blockade with intravenous sodium bicarbonate and supportive care. This report highlights the importance of strict supervision and monitoring while administering antiarrhythmic drugs in neonates and prompt institution of appropriate remedial action for treatment when toxicity is suspected.